Optimum Computer Design of External Spur Gears - Stratton, John (My University, 1972)
Using established spur gear design practice, a user-oriented computer-aided design package is created by which a user requires minimal knowledge of, or experience in either FORTRAN, optimization or gear design. although this practice is risky since the designer a judgement should be employed to the same extent as in a manual design. The package is essentially material independent with options to specify the design variables as constant, standard or variable. The great flexibility incorporated in the routine enables the designer a full range of design features from control to power gearing. The structure of the package enables implementation of new theory or new optimization criteria with relative ease.
Keywords: Computer Design; External Spur; Gears; computer-aided design